Cleidocranial dysplasia: Case report and literature review - CHAI An; LEI Rongchang; QU Binbin; LI He; SHAO Qi; JIANG Zhisheng (Kouqiang hemian waike zazhi)
Cleidocranial dysplasia (CCD) is rare, which was usually found accidentally when they consulted a doctor due to oral problems. Clinically, it is necessary to improve relevant examinations and deal with oral and maxillofacial problems for such cases. It is essential to rebuild a stable occlusal relationship and improve the quality of life. This paper reports a rare case of CCD and reviews the current literature on the clinical manifestations、etiology、diagnosis and various treatment modalities of this disease.